Odpowiedź :
Odpowiedź i szczegółowe wyjaśnienie:
Wyznaczenie zmiennej h ze wzoru:
[tex]P=\dfrac{a+b}{2}\cdot h\ /\cdot 2\\\\2P=(a+b)\cdot h\ /:(a+b)\\\\h=\dfrac{2P}{a+b}[/tex]
Wyznaczenie zmiennej b ze wzoru:
[tex]P=\dfrac{a+b}{2}\cdot h\ /\cdot 2\\\\2P=(a+b)\cdot h\ /:h\\\\\dfrac{2P}{h}=a+b\\\\b=\dfrac{2P}{h}-a[/tex]
P=a+b/2 *h /*2
2p= (a+b) *h /:(a+b)
h=2P/a+b
Zmienna b
P=a+b/2 * h /*2
2p=(a+b)*h /:h
2P/h = a+b
b= 2P/h -a
2p= (a+b) *h /:(a+b)
h=2P/a+b
Zmienna b
P=a+b/2 * h /*2
2p=(a+b)*h /:h
2P/h = a+b
b= 2P/h -a